Violence against indigenous women: literature, activism, resistance - Hargreaves, Allison (Indigenous studies series, 2017)
"Indigenous communities have been organizing against violence since newcomers first arrived, but the cases of missing and murdered women have only recently garnered broad public attention. Violence Against Indigenous Women joins the conversation by analyzing the socially interventionist work of Indigenous women poets, playwrights, filmmakers, and fiction-writers. Organized as a series of case studies that pair literary interventions with recent sites of activism and policy-critique, the book puts literature in dialogue with anti-violence debate to illuminate new pathways toward action."--